Determinants of Household Risky-Asset Participation and Portfolio Quality: A Critical Review - Hu, Yichen (Exploring Science Academic Conference Series, 2026)
Household participation in risky-asset markets matters for long-term wealth accumulation. However, many households still avoid these markets. Some households enter the market, but then make weak investment choices. This review examines the main determinants of household risky-asset participation and portfolio quality. The review compares studies on entry costs, wealth constraints, financial capability, behavioural bias, trust, financial advice, and digital investment platforms. It finds that risk aversion alone does not explain non-participation. Non-participation is also linked to participation costs, perceived complexity, low wealth, liquidity constraints, and limited risk capacity. After households enter the market, portfolio quality depends on financial literacy, behavioural bias, diversification, fees, and trading behaviour. Digital finance has mixed effects. Robo-advisors may help households access diversified and low-cost portfolios. However, app-based trading platforms may encourage speculative and attention-driven trading. The review concludes that better market access does not automatically lead to better investment outcomes. Policy and future research should therefore focus on portfolio quality and household financial welfare, rather than participation rates alone.